The Economic Competitiveness and Inclusive Development Nexus: Empirical Evidence from 101 Economies - Neagu, Olimpia; Teodoru, Mircea Constantin (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
The paper explores the association between economic competitiveness and inclusive development in 101 economies based on data provided by the 2018 WorldEconomic Forum reports. Coefficients of ranks correlation and cluster analysis are used in this view. The values of Competitiveness Index and of Inclusive Development Index delivered by the 2018 World Economic Forum reports are considered. Economic competitiveness and inclusive development are positively associated in our sample of 101 economies and the correlation is stronger in the emerging countries as in the group of advanced economies. Among the advanced economies the mean scores of GCI and IDI are higher than in the group of emerging countries showing a better coordination of economic and institutional factors driving competitivity as well as inclusiveness. Countries belonging to a geographical region/continent/economic group are not grouped in the same cluster, emphasizing disparities among countries at regional/continental/economic group level. In the group of emerging economies, the disparities regarding competitivity and inclusiveness are lower than those among the advanced economies, the clusters are closer to one another and they are more homogeneous. Greater competitivity and economic performance can generate socioeconomic inequity that should be corrected through appropriate economicand social policy measures aimed to lead to wider distrbution of income and social inclusiveness.